Beyond Environmental Regulations: Exploring the Potential of "Eco-Islam" in Boosting Environmental Ethics Within SMEs in Arab Markets - Abdelzaher, Dina M.; Abdelzaher, Amir (Journal of business ethics, 2017)
The recent global increase in environmental regulation does not necessarily signal improvement in firms' ecological imprints. Like many markets, the Arab world is struggling to implement environmental compliance measures among local firms. For Arab countries, the reliance solely on formal policies to improve local firms' ecological footprints may be risky given the evident institutional challenges to enforce environmental regulations, specially post the Arab Spring. Drawing from the literature highlighting the merits of combining formal and informal controls to ensure successful implementation of a strategy, we argue that the emphasis for regulation must be accompanied by an emphasis for developing environmental ethics of individuals, who are the expected implementers of any environmental policy. In that light, we propose that the Eco-Islam phenomenon can serve as an influential and effective foundation for building organizational cultures with stronger environmental ethics among local small and medium enterprises (SMEs). We explain the underlying maxims of Eco-Islam then conduct qualitative research among experts preaching or practicing the concept to gain better insights into the potential of leveraging it in Muslimmajority Arab countries. Finally, we conclude with insightful implications for local SMEs in the region.